2020
DOI: 10.33019/society.v8i1.170
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Parents' Sexual Education in Bugis-Makassar Families

Abstract: False interpretations of sex make sex education less prioritized by parents in educating their children. This condition is considered as the cause of increased child abuse, violence, and sex crimes. This research aims to reveal the social construction of parents’ sexual education Bugis-Makassar families. The research used a qualitative approach with the paradigm of constructivism. The analysis model was conducted through the interpretation and understanding of data collected through interviews and observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
3
0
5
Order By: Relevance
“…For parents of children with Down syndrome, based on the results of the study, it is known that they apply more about children's boundaries in socializing, when in the previous phase the parents introduced social boundaries, in this phase the child must be able to apply them. Sexual education material given based on age stages as found in this study is relevant to the results of research [32] which found that for parents in the Bugis Makassar family, constructions education there are 4 sexual namely 1) sexual education is teaching about genitals; 2) teaching sexual intercourse procedures; 3) differentiating the roles of men and women, and; 4) the process of teaching manners to get along with the opposite sex. These four constructs are illustrated in the stages of providing sexual education to children with Down syndrome as in the results of this study.…”
Section: A Sexual Education Materials For Children With Down Syndromementioning
confidence: 70%
“…For parents of children with Down syndrome, based on the results of the study, it is known that they apply more about children's boundaries in socializing, when in the previous phase the parents introduced social boundaries, in this phase the child must be able to apply them. Sexual education material given based on age stages as found in this study is relevant to the results of research [32] which found that for parents in the Bugis Makassar family, constructions education there are 4 sexual namely 1) sexual education is teaching about genitals; 2) teaching sexual intercourse procedures; 3) differentiating the roles of men and women, and; 4) the process of teaching manners to get along with the opposite sex. These four constructs are illustrated in the stages of providing sexual education to children with Down syndrome as in the results of this study.…”
Section: A Sexual Education Materials For Children With Down Syndromementioning
confidence: 70%
“…Tahapan ini merupakan pembentukan manusia yang berlangsung secara menerus dalam kehidupan dunia yang dapat dilihat pada kegiatan fisik amupun mental. Apabila proses ekternalisasi telah dilalui dan telah didapat maknanya maka masyarakat selanjutnya akan menginterpretasikan makna tersebut kedalam bentuk penilaiannya masing-masing (Awaru, 2020). Hasil penilaian atau interpretasi tersebut yang kemudian dianggap sebagai produk berpikir yang dihasilkan oleh individu atau masyarakat.…”
Section: Konstruksi Sosial Citra Univeritas Negeri Makassar Pada Maha...unclassified
“…Konstruksi citra Universitas Negeri Makassar terbentuk pada diri individu bisa saja dipengaruhi oleh dirinya sendiri, oleh teman sebaya, iklan ditelevisi atau pengaruh dari sekolah dan juga dari orang tua individu itu sendiri. Sebagaimana teori konstruski sosial dalam (Awaru, 2020) (Jahidin & Ahmad, 2019) bahwa: dalam proses pengembangan, individu melalui tindakan dan interaksinya secara terus menerus menciptakan sebuah kenyataan yang dimiliki bersama, yang secara faktual bersifat obyektif dan memilki arti subyektif, yang dalam proses pembentukannya melalui tiga tahap yaitu eksternalisasi, obyektivasi dan internalisasi yang ketiga berlangsung secara terus menerus.…”
unclassified
“…Yang tidak untuk di bicarakan di atau didiskusikan didepan public atau orang banyak. Seks dalam pandangan masyarakat Bugis-Makassar hanyalah milik bagi orang dewasa yang telah menikah [1], [2].…”
Section: Pendahuluanunclassified